Cabine de aeronaves e tecnologia assistiva: contribuições de um estudo de prospecção - Campese, Carina (2014)
The demand for air travel has grown each year, both in Brazil and abroad. Researches also indicate an estimated worldwide increase in elderly and obese people. In regards to people with disabilities, studies show that approximately 15% of the world population has some kind of disability and only in Brazil it´s believed that this population represents 25%. There is a growing participation of people with disabilities and people with special needs (such as the elderly and obese) in society, including the use of air transport. These people take use of assistive equipment (assistive technology) in their daily lives, and how air passengers, they take these products on board. That´s the focus of this study: a study in assistive technology. Thus, the goal is to identify products of assistive technology and understand the trends in this field to support future discussions about the implications for aircraft cabin design. First, a literature review was performed in order to better understand assistive technology and universal design. Then, collecting data through research at fairs, internet, survey and interviews related to assistive technology companies was performed. Such procedures indicated what kind of assistive technology products are used and what the emerging products are. Data were collected and analyzed from a descriptive perspective. The conclusions of the study were then formulated. They indicate a large number of assistive technology products for people with physical and visual disabilities and a big trend in multifunctional and electronic products. Assistive technology products bring great impact to the current and future design of the passenger cabin.